2006
DOI: 10.1073/pnas.0511197103
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated ion channels in the axon initial segment of human cortical pyramidal cells and their relationship with chandelier cells

Abstract: The axon initial segment (AIS) of pyramidal cells is a critical region for the generation of action potentials and for the control of pyramidal cell activity. Here we show that Na ؉ and K ؉ voltagegated channels, together with other molecules involved in the localization of ion channels, are distributed asymmetrically in the AIS of pyramidal cells situated in the human temporal neocortex. There is a high density of Na ؉ channels distributed along the length of the AIS together with the associated proteins spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(171 citation statements)
references
References 66 publications
6
161
4
Order By: Relevance
“…Together, these results implicate K ϩ channels containing Kv1.2 subunits, either in a heteromeric or homomeric mixture (11,36,37) are the mediators of the D-current responsible for axonal spike repolarization. Immunocytochemical studies reveal the prominent expression of Kv 1.2 channels in axons and axonal terminal fields throughout the brain (6,11,38,39). In the neocortex, Kv1.2 is of particularly high density in the more distal portions of the axon initial segment of cortical pyramidal cells (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these results implicate K ϩ channels containing Kv1.2 subunits, either in a heteromeric or homomeric mixture (11,36,37) are the mediators of the D-current responsible for axonal spike repolarization. Immunocytochemical studies reveal the prominent expression of Kv 1.2 channels in axons and axonal terminal fields throughout the brain (6,11,38,39). In the neocortex, Kv1.2 is of particularly high density in the more distal portions of the axon initial segment of cortical pyramidal cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question is largely unknown. Immunocytochemical studies indicate that pyramidal cell axons contain a high density of transient and persistent Na ϩ currents, particularly in the axon initial segment and nodes of Ranvier (6)(7)(8) and at least Kv1.2 ␣-subunit containing K ϩ channels (6). In other preparations, Kv1.1, 1.2, and 1.6 ␣-subunits contribute to the formation of low-threshold K ϩ channels that are important in determining axonal excitability and axonal spike duration (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…63,64 Formation of this complex is mediated by Protein 4.1B binding to the intracellular portion of CASPR2 and is required for the clustering of voltage-gated potassium channels at juxtaparanodes. 65 These channels are involved in the rapid, saltatory conduction of nerve impulses, 66 and individuals from the CDFE cohort (with homozygous CNTNAP2 mutations) display reduced potassium channel (K v 1.1) localisation in hippocampal axons.…”
Section: Caspr2 and The Juxtaparanodementioning
confidence: 99%
“…Examination of Na v 1.1 colocalization with ␤IV-spectrin, which is associated with ankyrin-G and specifically clustered at AISs and nodes of Ranvier (Berghs et al, 2000;Komada and Soriano, 2002;Inda et al, 2006), revealed that the Na v 1.1-immunoreactive portions of the nerve fibers were the ␤IV-spectrin-immunoreactive AISs of PV interneurons (Fig. 5Ba,Bb,Bd).…”
Section: Na V 11 Protein Clusters Predominantly At Axon Initial Segmmentioning
confidence: 99%